2012
DOI: 10.3346/jkms.2012.27.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Improving Survival Rate of Patients with In-Hospital Cardiac Arrest: Five Years of Experience in a Single Center in Korea

Abstract: The aim of this study was to describe the cause of the recent improvement in the outcomes of patients who experienced in-hospital cardiac arrest. We retrospectively analyzed the in-hospital arrest registry of a tertiary care university hospital in Korea between 2005 and 2009. Major changes to the in-hospital resuscitation policies occurred during the study period, which included the requirement of extensive education of basic life support and advanced cardiac life support, the reformation of cardiopulmonary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
4
22
0
2
Order By: Relevance
“…It is reported that patients resuscitated early and observed in ICU may have longer life expectancy and the critical point here is early diagnosis (13). In our study we found that 58.1% of the interventions ended with exitus and 10.6% of the cases were transferred to ICU after the first intervention.…”
Section: Discussionsupporting
confidence: 59%
“…It is reported that patients resuscitated early and observed in ICU may have longer life expectancy and the critical point here is early diagnosis (13). In our study we found that 58.1% of the interventions ended with exitus and 10.6% of the cases were transferred to ICU after the first intervention.…”
Section: Discussionsupporting
confidence: 59%
“…9,33 In cases with an initial rhythm of VF/pVT, the ROSC was 72-64%, 24 hour survival was 35-41% and hospital discharge is 36-24%. 14,17,18,26 These rates are higher compared to those observed in cases with an initial rhythm of asystole. [18][19][20] In our study, the ROSC, the 24 hour survival and the hospital discharge rates of patients with an initial VF/pVT rhythm at the time of arrest increased from 26.8%, 24.2% and 22.2%, respectively before the introduction of code blue (Group 1) to 73.27%, 75.8% and 77.8%, respectively, after code blue (Group 2).…”
Section: Discussionmentioning
confidence: 60%
“…The ROSC with an initial rhythm of asystole was observed to be as low as 35%. 26 24 hour survival (10-35%) and hospital discharge rates (5-7.5%) were also low. 9,33 In cases with an initial rhythm of VF/pVT, the ROSC was 72-64%, 24 hour survival was 35-41% and hospital discharge is 36-24%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations